Practical implications of the organizational commitment model in healthcare: the case of nurses - Rodríguez-Fernández, María Mercedes; Herrera-Ballesteros, Juan; De-las-Heras-Rosas, Carlos Javier; Ciruela-Lorenzo, Antonio Manuel (Wiley, 2024)
Background. In addition to the usual difficulty of managing human capital in any organization, healthcare institutions have other problems to solve arising from the circumstances and the very nature of the work they perform, such as the ethical pressure on sta6, emotional exhaustion, the distribution of work shifts, or the general shortage for nurses. In many cases, this situation has an impact on the quality of care. Objective. .e main objective of this research is to compile, in a single document, human resource practices that help health centre managers improve results in terms of performance and quality of care, as well as avoid the intention of abandoning the job, speci9cally related to the work of nurses. Methods. To this end, a systematic literature review has been performed based on 229 papers published in the Web of Science database, from which the practical implications for nurses proposed by these authors have been extracted. Results. .e main results suggest that developing a6ective commitment helps to improve organizational performance and enhance patient safety culture. Furthermore, improving communication and meaningfulness of work, recognition by superiors, or job >exibility would improve the quality of outcomes, for the work of nurses. Conclusions and Implications for Nursing. Stimulating normative commitment, reducing excessive control, and paying attention to job burnout and job stress help combat the intention of voluntary turnover or leaving the job, especially in the case of nurses
Keywords: Psicología de las organizaciones; Personal sanitario - Gestión; Enfermeras - Gestión; Healthcare; Organizational commitment; Nursing